MY NAME IS RED: WESTERN INFLUENCE AND CLASH OF CULTURE - Wicaksono, Bagus Prawira Satrio; Sakinah, R Myrna Nur (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2024)
This article mainly focuses in exploring the impacts of Western influence on Ottoman culture especially depicted in Orhan Pamuk's novel, My Name Is Red. It learns the ways in which Western artistic styles, philosophies, and social norms which spread and clashed with traditional Ottoman values and practices. Using literary analysis method which focused in related materials, related sources, and the novel itself. This analysis delves and try to find roots of specific examples of cultural conflict that might be caused by western influence, such as exploring the tension happened in the novel between traditional miniature painting style and Western oil painting, where painter who deeply rooted to traditional ways, struggling to adapt with many new techniques introduced and developed by western artists. Next is the clash between Islamic and Christian worldviews which intensified because of the existing western influence, and challenges faced by Ottoman women in navigating a rapidly changing society and even how unsatisfied they are with the current system. Ultimately, the study aims to explain the complex interplay between tradition and modernity in the context of colonial encounter and cultural exchange and eventually answers why the problem happen and how to avert, adapt, or even understand the reasoning behind those cultures.